9(x+1)-2(2-3x)=-10

Simple and best practice solution for 9(x+1)-2(2-3x)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+1)-2(2-3x)=-10 equation:


Simplifying
9(x + 1) + -2(2 + -3x) = -10

Reorder the terms:
9(1 + x) + -2(2 + -3x) = -10
(1 * 9 + x * 9) + -2(2 + -3x) = -10
(9 + 9x) + -2(2 + -3x) = -10
9 + 9x + (2 * -2 + -3x * -2) = -10
9 + 9x + (-4 + 6x) = -10

Reorder the terms:
9 + -4 + 9x + 6x = -10

Combine like terms: 9 + -4 = 5
5 + 9x + 6x = -10

Combine like terms: 9x + 6x = 15x
5 + 15x = -10

Solving
5 + 15x = -10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 15x = -10 + -5

Combine like terms: 5 + -5 = 0
0 + 15x = -10 + -5
15x = -10 + -5

Combine like terms: -10 + -5 = -15
15x = -15

Divide each side by '15'.
x = -1

Simplifying
x = -1

See similar equations:

| 10.08m+3.92-6m=72 | | 8+3y=38 | | 8x^2+2x=23 | | 4+3e^5x=27 | | X-43=21 | | 11n-88=-66 | | (6i)i= | | 4p-q=35 | | -0.2x-8=x+4 | | -0.2x-15=x+9 | | B+13=-50 | | p+q=10 | | 27-3w=-9 | | 9-3/3*5+10= | | sin(7x-14)=cos(18x+4) | | Y=0.8(220-y) | | 4e^3x=3 | | 108-12w=96 | | 1320=40k | | 3x=4y-6 | | (z^2)+2z+1+2i=0 | | H(-2)=-2/2 | | 3y-12=4 | | 12m-5-m+6= | | 7x-9=2x+7 | | 5(v-9)-9=-4(-6v+9)-7v | | (X-75)/7=1.18 | | 40*x=7500 | | 2x^2-33=39 | | 9/5=135/x | | 9y-27=-45 | | 3x+2+2x-17=90 |

Equations solver categories